Dukungan keluarga pada pasien gagal ginjal kronik yang menjalani hemodialisis: Analisis kasus etik - Anifan, Muhammad Nur; Arofiati, Fitri (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: The accumulation of toxins and fluid in the body due to decreased kidney function can lead to various potentially life-threatening systemic complications. Adherence to strict fluid restrictions is crucial to prevent intravascular fluid overload, which can increase the risk of edema, hypertension, and cardiovascular disease. Family support is an important social factor influencing health behaviors in patients with chronic kidney disease (CKD). Purpose: To describe in depth the clinical phenomena, patient responses, and the role of family support in improving adherence to hemodialysis therapy in patients with chronic kidney disease (CKD). Method: This case study was conducted in a hemodialysis unit at a healthcare facility on March 11, 2025. The subject was a 65-year-old female patient diagnosed with Chronic Kidney Disease (CKD) undergoing twice-weekly hemodialysis. Results: Two ethical dilemmas were identified in the case: autonomy and beneficence. Autonomy allows patients to make informed choices regarding their treatment options. Beneficence, in the form of healthcare professionals' obligation to provide the best possible care for the patient's well-being. Conclusion: Family support has been shown to be crucial in maintaining motivation, assisting decision-making, and improving adherence to therapy.   Keywords: Chronic Kidney Disease; Case Study; Family Support.   Pendahuluan: Akumulasi toksin dan cairan dalam tubuh akibat penurunan fungsi ginjal ini dapat menimbulkan berbagai komplikasi sistemik yang berpotensi mengancam jiwa. Kepatuhan terhadap pembatasan cairan yang ketat untuk mencegah kelebihan cairan intravaskular yang dapat meningkatkan risiko edema, hipertensi, dan penyakit kardiovaskular. Dukungan keluarga (family support) merupakan faktor sosial penting yang memengaruhi perilaku kesehatan pasien kronis.  akut Tujuan: Untuk menggambarkan secara mendalam fenomena klinis, response pasien, serta peran dukungan keluarga yang dapat diberikan dalam kepatuhan menjalani terapi hemodialisis pada pasien dengan Chronic Kidney Disease (CKD). Metode: Penelitian dengan desain studi kasus (case report) yang dilakukan di unit hemodialisis salah satu fasilitas pelayanan kesehatan pada tanggal 11 Maret 2025. Subjek penelitian adalah seorang pasien perempuan berusia 65 tahun dengan diagnosis Chronic Kidney Disease (CKD) yang menjalani terapi hemodialisis dua kali seminggu. Hasil: Terdapat dua Dilema Etik pada kasus yaitu Autonomy dan Beneficence. Autonomy pada pasien berhak menentukan pilihan terhadap pengobatan yang dijalaninya. Kemudian Beneficence berupa tenaga kesehatan memiliki kewajiban untuk memberikan perawatan terbaik demi kebaikan pasien. Simpulan: Dukungan keluarga terbukti sangat penting dalam menjaga motivasi, membantu pengambilan keputusan, serta meningkatkan kepatuhan terhadap terapi.   Kata Kunci: Chronic Kidney Disease; Dukungan Keluarga; Studi Kasus.